EVALUATION OF IRAN-DEFICIENCY ANEMIA BY SERUM FERRITIN ASSAY IN SEVE-YEAR-OLD CHILDREN - M Ghaemi; M Kimiagar; G Sadigh; M Navab (Tehran University of Medical Sciences, 1979)
Serum Ferritin (SF) levels in 734 seven-year-old children was measured by a radioimmuno assay method, and its possible relation-ship with hemoglobin, hematocrit and MCHC was investigated. The results showed there was positive correlation between SF with hemo-globin, hematocrit and MCHC values.